Highly enhanced visible light photocatalytic activity of CeO2 through fabricating a novel p–n junction BiOBr/CeO2 - Wen, Xiao-Ju; Zhang, Chang; Niu, Cheng-Gang; Zhang, Lei; Zeng, Guang-Ming; Zhang, Xue-Gang (Catalysis communications, 2017)
CeO2 microplates were synthesized by a sol-gel auto-combustion method. BiOBr nanosheets were then deposited onto the surface of CeO2 via a facile deposition–precipitation method with the assistance of ethylene glycol. The as-prepared BiOBr/CeO2 samples were characterized by various analytical techniques. The BC-2(Ce/Bi molar ratios is 2) sample exhibited the highest photocatalytic activity. The RhB was degraded (97.3%) under visible light irradiation within 20min. Furthermore, the BC-2 also exhibited superior degradation activity towards methyl blue (MB) and phenol. The enhanced photocatalytic performance could be ascribed to the enhanced light absorption and the improved separation of photogenerated charge carriers through forming a p-n heterojunction. [Display omitted] •BiOBr/CeO2 was prepared via a deposition–precipitation method with the assistance of ethylene glycol.•The BC-2(Ce/Bi molar ratios is 2) sample exhibited the highest photocatalytic activity.•Enhanced photocatalytic activity was due to forming a p-n heterojunction between BiOBr and CeO2.